Systemic effects of hypophosphatasia characterization of two novel variants in the ALPL gene - Martínez-Heredia, Luis; Muñoz-Torres, Manuel; Sanabria-de la Torre, Raquel; Jiménez-Ortas, Ángela; Andújar-Vera, Francisco; González-Cejudo, Trinidad; Contreras-Bolívar, Victoria; González-Salvatierra, Sheila; Gómez-Vida, José María; García-Fontana, Cristina; García-Fontana, Beatriz (Frontiers in Endocrinology, 2024)
Hypophosphatasia (HPP) is a metabolic inborn error caused by mutations in the ALPL gene encoding tissue non-specific alkaline phosphatase (TNSALP) leading to a decreased alkaline phosphatase (ALP) activity. Although the main hallmark of this disease is bone involvement it presents great genetic and clinical variability, which is regarded as it a systemic disease. In the present study, two previously undescribed heterozygous mutations (L6S and T167del) have been identified by Sanger sequencing in the ALPL gene of two Spanish families. These mutations are associated with non-pathognomonic symptoms of HPP. Prediction tools coupled with structural modeling targeted critical residues with important roles in protein structure and function. In vitro results demonstrated low TNSALP activity and a dominant negative effect on both mutations. The results of the characterization of these variants suggest that the pleiotropic role of TNSALP leads to the systemic effects observed in these patients highlighting digestive and autoimmune disorders associated with TNSALP dysfunction. The importance of identifying and geno-phenotypically characterizing each mutation at structural and functional levels is very useful to anticipate potential comorbidities, providing personalized counseling and treatment for each patient considering the extra-skeletal manifestations of HPP.